Soil water repellency of two disturbed soils contaminated with different agricultural microplastics tested under controlled laboratory conditions - Železnikar Špela; Drobne Damjana; Hočevar Matej; Noč Matic; Pintar Marina (Geoderma)
Soil water repellency (SWR) significantly affects plant growth, along with surface and subsurface hydrology, posing a challenge for agricultural productivity and environmental sustainability. Nowadays, the occurrence of microplastics (MP) in the environment, particularly from agricultural practices, raises concerns about MP impact on soil properties. Among them, SWR is affected by hydrophobicity of MP particles detected in soils. This study introduces a method and presents results of a screening test to assess the effects of MP on SWR, utilizing Water Drop Penetration Time (WDPT) analysis under controlled laboratory conditions in destructed soil samples. We compared SWR of two soil types differing in portion of sand, loam and clay. Soils were mixed with three different types of MP originating from agricultural mulch films: low-density polyethylene (LDPE), biodegradable polybutylene adipate terephthalate (PBAT), and starch-based biodegradable plastics (Starch). The MP were milled to a uniform size range of some 10 to 300 μm and mixed with the soil samples. WDPT measurements were taken immediately after mixing and recorded for up to 60 s in order to find MP concentration levels at which strongly or more severely water repellency is inducted on soil samples. Our findings reveal that both, soil type and MP type significantly influence SWR, where there are notable differences observed between bio-based (Starch based) and non-bio-based (LDPE and PBAT) plastics’ effects on SWR in the two tested soil types. Data highlights the distinct behaviour of Starch in altering soil hydrophobicity, prominently different from the impact of both PBAT and LDPE. The measurement technique we have developed for quantifying SWR levels could be used for both research applications and the dissemination of findings. It can significantly enhance decision-making processes regarding the selection of optimal plastic alternatives for agricultural use.